THE ROLE OF GUS IQDAM'S DA'WAH IN BUILDING SPIRITUAL PEACE IN MODERN SOCIETY - Anwar, Khoirul; Nurhuda, Abid; Aziz, Thariq; Al Fajri, Muhammad (Jurnal Riset Mahasiswa Dakwah dan Komunikasi, 2024)
The increasingly rapid development of technology and science makes most people feel empty, anxious, and far from the meaning of life, so they need calm and peace in the spiritual field, one of which is by listening to and following the studies of young preachers. Among the many preachers, Gus Iqdam is a figure who is very popular with almost all groups of people. So this research aims to describe the role of Gus Iqdam's preaching in helping to solve the complex problems of modern society. The method used is descriptive qualitative, with a descriptive analysis model accompanied by a literature study approach technique. The results of this research show that the role of Gus Iqdam's preaching in building spiritual peace in modern society includes inviting people to repent and do good, using slang language that is easy for people to understand, then prioritizing humility, inviting communication, and looking positively at all humans who often do things. sin so that many modern people flock to follow all his lectures, both in person and online. There were even several community figures who admitted to Gus Iqdam that they could live a better life, such as a woman named Mey, former thug Hoho Al-Kaff, to YouTube artist, Agus Kotak.